Engenharia de tráfego em redes IP : estudo e aplicação de ferramentas de medição - Ferreira, Ana Elisa Leitão Alonso (2008)
Quality of service is a necessity even more present in such a way for users as for service suppliers, in special for service of Internet access. The end users desire to increase its degree of satisfaction with the services and demand guarantees to pass through real time and critical mission applications, on the other hand the operators desire to increase its profits offering aggregate value services. The implementation of QoS mechanisms allows the differentiated treatment of the some profiles of traffic, however the achievement of the QoS parameters commited with the customers via SLAs - Service Level Agreements is possible only with the otimization of the network resources and its constant measurement. This work presents a survey of the main topics related to the quality of service in IP backbones, giving emphasis to traffic engineering and the measurement as basic elements so that it is possible to achieve the customers requirements and even though to plan quality goals to be reached. Despite these not being new concepts they are extremely important and find many difficulties for its practical use. Complementing this survey, diverse tools developed for the international community of research had been analyzed. Amongst these tools, two had been selected for tests carried through the equipment homologation for UFF backbone. It was made still a study in three brazilian carries to verify the use of the traffic engineering and measurement tools in the management of its networks.